Pengaruh Penggunaan Metode Perekatan Celup Dan Non Celup Terhadap Kekuatan Impak Pada Pembuatan Batu Grinda 4'inch - TARMUJI, TARMUJI; , Bambang Waluyo F. ST, MT; , Ir masyrukan MT (2015)
Burrs is a tool that serves to grind the workpiece at first grinding to grind bend shown only work in the form of hard metal such as iron and stainless steel. Grinding may also aim to hone workpieces such as knives and chisels, or can also be used as smoothing results sebagaibenda work cutting, smoothing welds, forming an arch on the workpiece is angled, prepare the surface of the workpiece to weld, and so forth. In this study, using a grinding own design that aims to determine how much kekeuatan homemade grinding with grinding stone in the market. After the manufacture of grinding to a size of 4 inches gengan composition as it has been determined that the slag coarse mesh to 12-50 g adhesive epoxy resin composition 2.5G, Hardener 2.5 g fiber together weighing 3.1 to mix well then fine slag mesh 40- 30 g, adhesive epoxy resin composition 2.5 g, 2.5 g hardener together weighed 3.1 g fiber mix well. Furthermore, the composition of the mixture is inserted into the mold (mold) which is then compacted in a press machine with a force of 3 tons for 1 jam.Sesudah was done sintering temperature 140o C for 1 hour with a drying machine (oven). After grinding stone so then do impact test of each millstone were then performed the analysis of the test results. Testing was conducted on the impact testing and obtained results impact the average value of a millstone manufacturer LIPPRO has the highest value that is equal to 0.0342 joules / mm2. While millstone result of the design himself with adhesive non dye method has a lower value is 0.0125 joule / mm2 and millstones were using dye has a value of 0.0188 joule / mm2.